Effect of light intensity on the aggressiveness and oxidative stress in female cichlid Tilapia Rendalli - Carvalho, T. B.; Mendes, C. C.; De Almeida, E. A. [UNESP]; Gonçalves-de-Freitas, E. [UNESP] (My University, 2014)
Physical changes due to degradation or handling to provide improvements in animal husbandry usually modify the aquatic environment and, one of the environmental variables that can be changed is the luminance. Increased light intensity, for instance, can increase the production of reactive oxygen species (ROS) that cause molecular damage to cellular structures with consequent functional impairment and loss of vital functions. Additionally, increased light intensity affects aggressiveness in territorial fish, leading to different levels of social stress, which can increase the effects of oxidative stress and ROS activity. Thus, the aim of this chapter was to test the influence of light intensity on the agonistic behavior and oxidative stress in female of Tilapia rendalli. We compared two treatments referred here as low (253.56 ± 62.25 lx) and high light intensity (1435.92 ± 481.40 lx), each one under two conditions: 1. Social Condition, : where animals were isolated for 96 h and paired (resident-intruder paradigm) for 1 h;. and 2. Isolation Condition (baseline) where: fish were isolated for 96 h. The latency to first fighting and for hierarchical settlement was similar in the two light intensities, but the high light intensity decreased the frequency of attacks and displays in winner fish. On the other hand, there was no difference between the frequencies of aggressive events displayed by loser in both treatments. Catalase did not differ between the two intensity or conditions for all animals. Thus, the light intensity reduces the aggressive interactions, and this influence is related to social rank in female of T. rendalli. However, the effects of aggressive interactions were not translated into variations of catalase, showing that oxidative stress is not associated to such a behavioral or environmental modifications.
Keywords: Catalase; Energetic expenditure; Luminance; Social hierarchy; Stress